Effects of Microwave-Assisted Extraction Parameters on the Recovery Yield and Total Phenolic Content of Vernonia amygdalina Leaf Extracts with Different Methods of Drying - Alara, Oluwaseun Ruth; Nour, A. H.; Siti Kholijah, Abdul Mudalip; Olalere, Olusegun Abayomi (Kowsarmedical, 2018)
Vernonia amygdalina leaf has a significant importance in food and traditional medicine. It has been reported to possess various pharmacological effects. This study was carried out to investigate the influence of microwave-assisted extraction factors on the extraction from V. amygdalina leaves. The results highlighted that an increase in temperature deteriorated the yields of V. amygdalina leaf. Thus, shade-dried samples gave the highest yields at the irradiation times of 10 and 2 min, microwave power of 500 and 600W, the temperature of 100 and 80°C, the feed-to-solvent ratio of 1:10, and ethanol concentration of 60% v/v using water and ethanol as the extracting solvents, respectively. Likewise, the antioxidant assay resulted in IC50 values of 260_1.1 _g/mL DPPH and 149.78_0.81_g/mL ABTS for water and 204_0.92_g/mL DPPH and 31.17_1.4_g/mL ABTS for ethanol. Therefore, the synergistic mechanism of mass and heat transfer may be accounted for the accelerated extraction due to microwave.